Analisis Yuridis Perselisihan Sebagai Alasan Perceraian: Studi Kasus Putusan Pengadilan Nomor 166/Pdt/G/2017/Pn.Jkt.Pst - Imansyah, Aiziza Puteri; Salam, Abdul (LPPM Universitas Jambi, 2022)
This study aims to examine whether there is a relationship between the principlesof accountability, transparency, and participation with the management of villagefunds in Natar District, South Lampung Regency. This study looked at the extent towhich villages apply the principles of Good Governance in managing village fundsin running village government. This is by enacting Law no. 6 of 2014 concerning theFinancial Management of Village Funds. The population in this study was thevillages of Natar District, South Lampung Regency. The analysis method usesmultiple linear regression with SPSS Version 25. Based on the results of hypothesistesting using the Pearson correlation test using SPSS v25 software, only onehypothesis is supported, namely the accountability variable. At the same time, theother two hypotheses, namely, the variables of transparency and participation, arenot supported. The management of village funds in villages in Natar District, SouthLampung Regency is good enough to apply the principles and rules regardingaccountability. However, the principles of transparency and participation in themanagement of village funds are still not maximally implemented.